Elevated Levels of High-Melting-Point Phosphatidylglycerols Do Not Induce Chilling Sensitivity in an Arabidopsis Mutant. - Wu, J. (1995)
Molecular species of phosphatidylglycerol that contain only 16:0, 18:0, and 16:1-trans fatty acids undergo the transition from liquid crystalline phase to gel phase at temperatures well above 20[deg]C. Several lines of evidence have been used to implicate elevated proportions of these high-melting-point molecular species as a major cause of plant chilling sensitivity. In the fatty acid biosynthesis 1 (fab1) mutant of Arabidopsis, leaf phosphatidylglycerol contained 43% high-melting-point molecular species[mdash]a higher percentage than is found in many chilling-sensitive plants. Nevertheless, the mutant was completely unaffected (when compared with wild-type controls) by a range of low-temperature treatments that quickly led to the death of cucumber and other chilling-sensitive plants. Our results clearly demonstrate that high-melting-point phosphatidylglycerols do not mediate classic chilling damage. However, growth of fab1 plants was compromised by long-term (>2 weeks) exposure to 2[deg]C. This finding and other observations are consistent with a proposition that plants native to tropical and subtropical regions have evolved many traits that are incompatible with long-term growth or development in cooler climates but that may confer selective advantages at high temperatures.